Modular assembly of MOF-derived carbon nanofibers into macroarchitectures for water treatment. Issue 32 (9th August 2022) - Zhang, Zishi; Wang, Chaohai; Yao, Yiyuan; Zhang, Hao; Na, Jongbeom; Zhou, Yujun; Zhu, Zhigao; Qi, Junwen; Eguchi, Miharu; Yamauchi, Yusuke; Li, Jiansheng
Abstract : A scalable strategy is established to generate macroarchitectures based on MOF-related nanofibers. The modular assembly of macroarchitectures with luffa-like structures exhibits high mechanical strength and low densities. Abstract : The organized assembly of nanoparticles into complex macroarchitectures opens up a promising pathway to create functional materials. Here, we demonstrate a scalable strategy to fabricate macroarchitectures with high compressibility and elasticity from hollow particle-based carbon nanofibers. This strategy causes zeolitic imidazolate framework (ZIF-8)-polyacrylonitrile nanofibers to assemble into centimetre-sized aerogels (ZIF-8/NFAs) with expected shapes and tunable functions on a large scale. On further carbonization of ZIF-8/NFAs, ZIF-8 nanoparticles are transformed into a hollow structure to form the carbon nanofiber aerogels (CNFAs). The resulting CNFAs integrate the properties of zero-dimensional hollow structures, one-dimensional nanofibers, and three-dimensional carbon aerogels, and exhibit a low density of 7.32 mg cm −3, high mechanical strength (rapid recovery from 80% strain), outstanding adsorption capacity, and excellent photo-thermal conversion potential. These results provide a platform for the future development of macroarchitectured assemblies from nanometres to centimetres and facilitate the design of multifunctional materials.